150k views
0 votes
Please help!!! If...........

Please help!!! If...........-example-1
User Glostas
by
4.3k points

2 Answers

9 votes

Answer:

The equation is 2x² + 3x - 1 and here f(x) is -1

Putting f(x) = -1.


f(x) = 2 {( - 1)}^(2) + 3( - 1) - 1


f(x) = 2 (1) - 3 - 1


f(x) = 2 - 3 - 1


f(x) = - 1 - 1


f(x) = - 2

For g(x) put as -1


g(x) = - ( - 1)


g(x) = 1

Last step,

-2 + 1 = -1

So, option ( a) is correct

User Bvaughn
by
4.5k points
1 vote

Answer:

-1

Explanation:

Simply plug in (-1) to both equations and add.

Equation 1:

2(-1)^2 = 2

3(-1) = -3

2 + -3 - 1 = -2

Equation 2:

-( - 1) = 1

Add both together:

-2 + 1 = -1

User Sameerah
by
4.7k points